Aphid Facultative Symbionts Aid Recovery of Their Obligate Symbiont and Their Host After Heat Stress - Heyworth, Eleanor R.; Smee, Melanie R.; Ferrari, Julia (Frontiers in Ecology and Evolution, 2020)
Environmental conditions affect insect fitness, with many species constrained by specific temperature ranges. Aphids are limited to temperate climates and it is hypothesized that this is partly due to their heat-susceptible obligate nutritional symbiont Buchnera. Aphids often carry additional facultative symbionts which can increase the host’s fitness after heat stress. Here we used the pea aphid (Acyrthosiphon pisum) and three of its facultative endosymbionts (Candidatus Regiella insecticola, Candidatus Fukatsuia symbiotica (X-type; PAXS), and Candidatus Hamiltonella defensa) to investigate how these species respond to heat stress and whether their presence affects the fitness of the host or the obligate symbiont. We exposed aphid lines to a single high temperature event and measured lifetime fecundity and population densities of both obligate and facultative symbionts. Heat shock reduced aphid fecundity, but for aphids infected with two of the facultative symbionts (Regiella or Fukatsuia), this reduction was less than in uninfected aphids. The population density of Buchnera was also reduced after heat shock, and only recovered in aphids infected with Regiella or Fukatsuia but not in uninfected aphids or those with Hamiltonella. Although heat shock initially reduced the densities of two of the facultative symbionts (Hamiltonella and Fukatsuia), all facultative symbiont densities recovered by adulthood. Two of the facultative symbionts tested therefore aided the recovery of the obligate symbiont and the host, and we discuss possible underlying mechanisms. Our work highlights the beneficial effects of protective symbionts on obligate symbiont recovery after heat stress and how facultative symbionts may affect the wider ecological community.